ROLE OF MEDIATION CENTRES IN DOMESTIC VIOLENCE CASES - kaur, Simarpreet; Das, Sukanya (International Journal of Psychosocial Rehabilitation, 2020)
Domestic Violence against women is rather common then we think. Every third women, since the age of 15, has faced violence of various forms in the country. Ninety five per cent of all domestic assaults in heterosexual relationships involve men attacking women. Men are socialized in this culture to expect to be in control, especially in their relationships to women. Men batter to maintain their control and their power leading often to domestic violence against the female partner. Relationship where domestic violence is present faces many challenges and something is needed to look into the problems and try to resolve them. One of the methods is mediation which is voluntary, party-centred negotiation process and a pre-litigation alternative. Mediation can help in resolving some issues but may not be of help in others. Hence the present paper focuses on the role of mediation centres in dealing with domestic violence cases.